Detecting Heat Leaks with Trapped Ion Qubits - Pijn, Daniel; Onishchenko, Oleksiy; Hilder, Janine; Poschinger, U. G.; Schmidt-Kaler, F.; Uzdin, R. (Physical Review Letters, 2022)
The concept of passivity has been conceived to set bounds on the evolution of microscopic systems initialized in thermal states. We experimentally demonstrate the utility of two frameworks, global passivity and passivity deformation, for the detection of coupling to a hidden environment. We employ a trapped-ion quantum processor, where system qubits undergoing unitary evolution may optionally be coupled to an unobserved environment qubit, resulting in a heat leak. Evaluating the measurement data from the system qubits only, we show that global passivity can verify the presence of a heat leak, which is not detectable by a microscopic equivalent of the second law of thermodynamics. Furthermore, we experimentally show that passivity deformation allows for even more sensitive detection of heat leaks, as compared to global passivity, and detect a heat leak with an error margin of 5.3 standard deviations, in a scenario where other tests fail.
CRIS-Team Scopus Importer:2023-03-27